Hepatic Hydrothorax: The Conundrum and the Oxymoron - Sachin Kumar; Yashwant Patidar; Rakhi Maiwall (Journal of Clinical Interventional Radiology ISVIR)
Hepatic hydrothorax (HH) is an infrequent but a well-known complication of portal hypertension. Medical management of this condition often fails, and there are no large randomized-controlled trials establishing the best treatment strategies. HH thus represents a formidable entity in the management of end-stage liver disease, and the only definitive treatment is liver transplantation. Despite documented ominous outcome, tube thoracostomy (TT) is still a widely practiced approach to HH mostly by the unaware primary care physician. This communication reports the occurrence of pleurosubcutaneous fistula as a presenting complication of TT in a patient with HH. TT should thus be avoided at all costs in this subset of patients because it is fraught with multiple complications. This report reinforces the importance of clinical education and awareness of these complications and outcomes of TT in a cirrhotic patient with HH.